2018
DOI: 10.5505/agri.2017.62443
|View full text |Cite
|
Sign up to set email alerts
|

Early and Long Period Follow-up Results of Low-Glycemic Index Diet for Migraine Prophylaxis

Abstract: The results of the study revealed that low glycemic index diet intake can be an effective and reliable method to reduce migraine attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 8 publications
2
34
0
2
Order By: Relevance
“…The befit was maintained at 90-day. Severity of attacks was reduced at both 30-and 90-day in the drug group but only at 90-day in the diet group [132].…”
Section: Carbohydratementioning
confidence: 85%
“…The befit was maintained at 90-day. Severity of attacks was reduced at both 30-and 90-day in the drug group but only at 90-day in the diet group [132].…”
Section: Carbohydratementioning
confidence: 85%
“…55 An earlier RCT also reported that a high omega-3 and low omega-6 fatty acid diet leads to the reduction of headache days, frequency and pain in people with chronic headaches. 66 Ketogenic 54 and low-glycemic index 50 diets have also been reported to be beneficial in certain people with migraine. 67 The benefit of these diets was expected given that earlier studies have reported a significant correlation between obesity and migraine headache 68,69 and avoiding unhealthy food has led to better outcomes in people with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…The mean frequency and severity of attacks as measured by the visual analog scale (VAS) decreased significantly after 3 months in the diet group compared with those in the medication group (P < .05). 50 In another randomized, cross-over dietary interventional trial, a low-lipid (lipid content <20% of the total daily energy intake) or a normal-lipid (between 25% and 30% of the total daily energy intake) diet was assigned randomly for 3 months and then the diets were crossed over for the following 3 months. A significant correlation between low-lipid diet and decrease in migraine attacks (2.9 ± 3.7; P < .001 vs baseline and P < .05 vs normal-lipid diet) was established.…”
Section: Dietary Risk Factorsmentioning
confidence: 99%
“…Such finding was also reported in other two clinical trials [ 32 , 33 ]. Furthermore, Evcili et al reported that adherence to a low-glycemic index diet, characterized by a high amount of zinc, resulted in a significant reduction in the frequency of migraine attacks [ 34 ]. In a case-control study, migraine patients had a lower diet quality (defined by Healthy Eating Index) than those without migraine.…”
Section: Discussionmentioning
confidence: 99%